The Relationship between Health Care Function and Family Coping Strategies with Hypertensive Dietary Adherence in Families with Hypertension - Hidayat, Taufik; Widniah, Any Zahrotul; Febriana, Annisa (Indonesian Journal of Global Health Research, 2024)
Hypertension is a global problem that can occur in all age groups and is commonly found in adults to the elderly. Hypertension can get worse when the patient has not been able to comply in maintaining his diet. The family has an important role in carrying out health care functions and maintaining family coping when one family member suffers from hypertension. Objective: This study aimed to analyze the relationship between health care function and family coping mechanisms with hypertensive dietary adherence in families with hypertension. This research method is descriptive correlational analytic with a cross sectional approach. The samples in this study were taken as many as 120 people using the quota sampling method on families in the Banjar Regency area in Martapura, West Martapura, East Martapura, Astambul, and Karang Intan sub-districts. Data was collected using questionnaires. Data were analyzed using the spearman rho test. The results showed a relationship between health care function and dietary adherence p Value 0.004 and no relationship between family coping strategies and dietary adherence p Value 0.648. This research is an input for families to improve family health care functions so that dietary compliance with hypertension sufferers increases.